2018
DOI: 10.3389/fnbeh.2018.00162
|View full text |Cite
|
Sign up to set email alerts
|

tDCS Modulatory Effect on Reading Processes: A Review of Studies on Typical Readers and Individuals With Dyslexia

Abstract: The possibility to use non-invasive brain stimulation to modulate reading performance in individuals with developmental dyslexia (DD) has been recently explored by few empirical investigations. The present systematic review includes nine studies which have employed transcranial direct current stimulation (tDCS) aiming at improving reading abilities in both typical readers and individuals with DD. Anodal tDCS over the left temporo-parietal cortex—a region which is typically involved in phonological and orthogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 63 publications
(119 reference statements)
3
33
1
Order By: Relevance
“…These results supported previous evidence that anodal stimulation (increased excitability) in the left temporo-parietal areas combined with concomitant cathodal stimulation (decreased excitability) of contralateral areas can modulate reading, as already showed in typically reading adults and in children and adolescents with dyslexia [ 62 , 80 ].…”
Section: Discussionsupporting
confidence: 91%
“…These results supported previous evidence that anodal stimulation (increased excitability) in the left temporo-parietal areas combined with concomitant cathodal stimulation (decreased excitability) of contralateral areas can modulate reading, as already showed in typically reading adults and in children and adolescents with dyslexia [ 62 , 80 ].…”
Section: Discussionsupporting
confidence: 91%
“…A possible progress in the treatment of this disorder could be achieved by the integration of these cognitive trainings with NIBS techniques (Vicario and Nitsche, 2013b), to foster the activation of the areas that are involved in compensatory processes in dyslexia. In this vein, the use of tDCS has been proposed (Vicario and Nitsche, 2013b; Cancer and Antonietti, 2018) and three recent double-blind, sham controlled studies assessed the effects of enhancing left parieto-temporal activation with anodal tDCS. No studies for the treatment of dyslexia with other NIBS techniques have been conducted so far.…”
Section: Methodsmentioning
confidence: 99%
“…A test-training-retest study showed the efficacy of RRT intervention on reading abilities of 14 junior high school students with DD, compared to a matched control group that received no intervention (Bonacina et al, 2015). Other test-training-retest small scale studies supported RRT efficacy in primary and junior high-school Italian students with DD, under different conditions (Cancer and Antonietti, 2017;Cancer et al, 2019).…”
Section: Rhythmic Reading Training (Rrt)mentioning
confidence: 99%
“…This lively search for DD brain basis is fostering a new wave of innovative treatments aiming at enhancing reading skills in an indirect way, by training the cognitive and perceptual skills potentially involved in the reading process (e.g., Thomson et al, 2012;Bhide et al, 2013;Flaugnacco et al, 2015;Cancer and Antonietti, 2018;Frey et al, 2019;Pecini et al, 2019). However, there remains a strong need to identify among old and new interventions the ones that are, first of all, effective in improving reading skills (Lorusso et al, 2006) and, secondly, use resources efficiently (Franceschini et al, 2013).…”
Section: Introductionmentioning
confidence: 99%